An experimental study on flexural strengthening of RC beams using CFRP sheets - Murad, Yasmin (International Journal of Engineering and Technology, 2018)
Â The use of carbon fiber reinforced polymer (CFRP) sheets is becoming a widely accepted solution for strengthening and repairing rein-forced concrete (RC) structures. To date, the behavior of RC beams, strengthened with 60Ëš and 45Ëš inclined CFRP sheets, has not clearly explained. An experimental program is proposed in this paper to investigate the flexural behavior of RC beams strengthened with CFRP sheets. CFRP sheets were epoxy bonded to the tension face to enhance the flexural strength of beams inducing different orientation angles of 0Ëš, 45Ëš, 60Ëš and 90Ëš with the beam longitudinal axis. The study shows that strengthening RC beams with CFRP sheets is highly influenced by the orientation angle of the sheets. The orientation angle plays a key role in changing the crack pattern and hence the failure mode. The influence of CFRP sheets was adequate on increasing the flexural strength of RC beams but the ductility of the beams was reduced. The best performance was obtained when strengthening RC beam obliquely using 45Ëš inclined CFRP sheets where the specimen experienced additional deflection and strength of 56% and 12% respectively and the reduction in its ductility was the least. It is recom-mended to strengthen RC beams, which are weak in flexure, using 45Ëš inclined CFRP sheets.Â Â